1997
DOI: 10.1046/j.1365-294x.1997.00175.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular scatology: the use of molecular genetic analysis to assign species, sex and individual identity to seal faeces

Abstract: Seals and commercial fisheries are potential competitors for fish and cephalopods. Research into the diet of British seal species has been based on conventional dietary analyses, but these methods often do not allow assignment of species identity to scat samples. We present a protocol for obtaining DNA from seal scat (faecal) samples which can be used in polymerase chain reactions to amplify both nuclear and mitochondrial DNA. This can provide a method of identifying the species, sex and individual identity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
197
1
3

Year Published

1999
1999
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 219 publications
(204 citation statements)
references
References 42 publications
3
197
1
3
Order By: Relevance
“…The use of DNA-based techniques for sex assignment of scats (e.g. Reed et al 1997) may allow assessment of sources of variation in diet composition in future studies.…”
Section: Comparison With Historical Studiesmentioning
confidence: 99%
“…The use of DNA-based techniques for sex assignment of scats (e.g. Reed et al 1997) may allow assessment of sources of variation in diet composition in future studies.…”
Section: Comparison With Historical Studiesmentioning
confidence: 99%
“…For example, this approach allowed Reed et al (1997) to determine the relative impacts of grey (Halichoerus grypus) and harbour (Phoca vitulina) seals on fisheries, and Hansen and Jacobsen (1999) to better interpret the feeding biology of mink (Mustela vison), otters (Lutra lutra) and polecats (Mustela putorius). In another example, assignment of field-collected scats to each of four sympatric Venezuelan carnivore species using mtDNA analysis, indicated that scat size overlapped considerably among species.…”
Section: Dietary Analysismentioning
confidence: 99%
“…Feces is a non-invasive sample that is easy to collect and contains a large amount of ecological information (Waits and Paetkau, 2005;Brinkman and Hundertmark, 2009). The development of techniques that utilize DNA collected through non-invasive sampling from wild animals, particularly feces, has created new opportunities for sex determination in wildlife (Reed et al, 1997;Ding et al, 1998;Oliveira and Duarte, 2013).…”
Section: Introductionmentioning
confidence: 99%